A nutrition programme using positive deviance approach to reduce undernutrition among urban poor children under-five in Malaysia: a cluster randomised controlled trial protocol - Chek, Lok Poh; Gan, Wan Ying; Chin, Yit Siew; Sulaiman, Norhasmah (Public Library of Science, 2022)
Background: Childhood undernutrition remains a public health issue that can lead to unfavourable effects in later life. These effects tend to be more devastating among urban poor young children, especially in light of the recent COVID-19 pandemic. There is an immediate need to introduce interventions to reduce childhood undernutrition. This paper described the study protocol of a nutrition programme that was developed based on the positive deviance approach and the evaluation of the effectiveness of the programme among urban poor children aged 3 to 5 years old. Methods: This mixed-method study will be conducted in two phases at low-cost flats in Kuala Lumpur. Phase one will involve a focus group discussion with semi-structured interviews to explore maternal feeding practices and the types of food fed to the children. Phase two will involve a two-armed cluster randomised controlled trial to evaluate the effectiveness of a programme developed based on the positive deviance approach. The programme will consist of educational lessons with peer-led cooking demonstrations, rehabilitation, and growth monitoring sessions. Intervention group will participate in the programme conducted by the researcher for three months whereas the comparison group will only receive all the education materials and menus used in the programme after data collection has been completed. For both groups, data including height, weight, and dietary intake of children as well as the nutritional knowledge and food security status of mothers will be collected at baseline, immediate post-intervention, and 3-month post-intervention. Expected results: The positive deviance approach helps to recognise the common feeding practices and the local wisdom unique to the urban poor population. Through this programme, mothers may learn from and be empowered by their peers to adopt new feeding behaviours so that their children can achieve healthy weight gain.